THE EFFECTS OF GENDER RELATIONS, AND RACIST IDEOLOGY ON FEMALE BLACK IDENTITY - 528, Mr. Deepak Kumar, Dr.Mamta Roy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the Afro-American community, gender relations and racism are made up of numerous interconnected segments that are difficult to comprehend. In this study, the impacts of gender relations and racism on female Black identity are investigated in two novels by Gloria Naylor, Linden Hills and Bailey's Cafe, and one novel by Marshall, The Chosen Place, the Timeless People. Marshall's concentration on racial issues is evident in the majority of her works, which depict cultural disparities between Americans and Africans. The novel's protagonist is also a woman who is subjected to racial discrimination in every way. Merle, the protagonist of the novel The Chosen Place, the Timeless People, shows the effects of racist persecution on Afro-American women. Merle's character is shaped by factors such as race, class, and gender. Although it is obvious that no Black woman writer can create a piece of art without taking race and gender into account, Marshall's works score higher in this regard due to the level of resilience shown by female characters when confronted with injustice.